Analyzing the Life Prediction of Spur Gear based on Vinyl Ester with Different Fibre Proportion. Issue 1 (1st July 2022) - Saketharaman, K.; Meenakshi, C.M.; Ravi, D.
Abstract: The gear is an essential part of every mechanical power transmission system, as well as most industrial rotating machinery. Gears may grow to dominate as the most effective mechanism for transmitting power in future machines due to their high degree of durability and compactness. The vinyl ester resin have high strength and low frictional of porous carbon material. The Vinyl ester resin is used as a reinforced material in plastic gear. In this work, Vinyl Ester and Glass fiber composite material with different proportions were equipped for strengthen cast plastic gear. The spur gear pair was used as the test gears, and the glass transition temperature and fatigue tests were used to determine the gear's life span. Finally, the composite gear has to be analyzed.